Advertising and identity construction : A cultivation analysis on health and beauty advertisements in Sabah - Chin, Ying Shin (2014)
Most identities are anchored in specific values; therefore the influence of western values on local identity construction has been a concern in Malaysia. The western values have been greatly promoted by the media, particularly the advertising. Therefore, this study aimed at examining the effects of TV advertising on identity construction among youth in Sabah, two western values namely individualism and materialism were the focus of the study. The influence of TV advertising on identity construction was explained using cultivation theory. A survey was conducted among 373 respondents who were selected from a local university in Sabah through multistage cluster sampling method. Focus group discussion was then conducted to obtain a deeper understanding of the influence of TV advertising. The results showed that local youth are more inclined towards individualistic identity than materialistic identity, exposure to TV advertising was a positive predictor of individualism and materialism adoption, however, only a small effect of TV advertising was found. The findings were discussed in relation to assumptions of cultivation theory, namely cumulative effects, mainstreaming effects and resonance effects. In conclusion, the findings essentially provided a new insight into the influence of health and beauty advertisements exposure on youth identity construction in Sabah.